Geo-Metadata Server: Metadata Entry Facility - Di Bono, Maria Grazia; Martinelli, Massimo; Salvetti, Ovidio (2004)
In the context of the Information System for Italian Research in Antarctica (SIRIA) project, the operating unit of the Institute of Information Science and Technologies has to study and realize a web system for the collection and the management of the metadata on Italian campaigns in Antarctica. The aim of this project report is to illustrate the realization and the possibilities provided by the module of Metadata Entry of the system Geo-Metadata Server (GMDS), that allows to all registered users belonging to PNRA research sectors, to store information on their own Antarctic data.